Smart Temperature‐Gating and Ion Conductivity Control of Grafted Anodic Aluminum Oxide Membranes - Lee, Min‐Jie; Chen, Yi‐Fan; Lee, Lin‐Ruei; Lin, Yu‐Liang; Zheng, Sheng; Chang, Ming‐Hsuan; Chen, Jiun‐Tai (Chemistry : a European journal, 2023)
Over the past few decades, stimuli‐responsive materials have been widely applied to porous surfaces. Permeability and conductivity control of ions confined in nanochannels modified with stimuli‐responsive materials, however, have been less investigated. In this work, the permeability and conductivity control of ions confined in nanochannels of anodic aluminum oxide (AAO) templates modified with thermo‐responsive poly(N‐isopropylacrylamide) (PNIPAM) brushes are demonstrated. By surface‐initiated atom transfer radical polymerization (SI‐ATRP), PNIPAM brushes are successfully grafted onto the hexagonally packed cylindrical nanopores of AAO templates. The surface hydrophilicities of the membranes can be reversibly altered because of the lower critical solution temperature (LCST) behavior of the PNIPAM polymer brushes. From electrochemical impedance spectroscopy (EIS) analysis, the temperature‐gating behaviors of the AAO‐g‐PNIPAM membranes exhibit larger impedance changes than those of the pure AAO membranes at higher temperatures because of the aggregation of the grafted PNIPAM chains. The reversible surface properties caused by the extended and collapsed states of the polymer chains are also demonstrated by dye release tests. The smart thermo‐gated and ion‐controlled nanoporous membranes are suitable for future smart membrane applications. Progress in solid‐state nanochannels development: A thermo‐responsive polymer poly(N‐isopropylacrylamide) (PNIPAM) brushes grafted anodic aluminum oxide (AAO) membrane by surface‐initiated atom transfer radical polymerization (SI‐ATRP) is presented. This thermo‐gated smart membrane shows a reversible surface wettability change, which allows the smart membrane to control the ion conductivity and ensures the dye release ability.